การผลิตซอร์บิทอลโดย Zymomonas mobilis TISTR 548 ด้วยการเลี้ยงแบบเฟดแบตช์ - พาคินทร์ เจริญทิพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
In this research sorbitol productions were carried out both in batch and fed-batch fermentations using Zymomonas mobilis TISTR 548 with 20% sucrose as a C-source in the rich culture medium. From factorial design experiments, the optimal conditions for sorbitol productions were initial pH of 6.5, 30 degree celsius and 48 h. In 250 ml Erlenmeyer flask under the optimal conditions, sorbitol yield and productivity of 18.56 g l[superscript -1] and 0.45 g l[superscript -1] h[superscript -1] were obtained. Scaling up to a 2 l bioreactor with the working volume of 1.0 l, the sorbitol yield and productivity were 24.54 g l[superscript -1] and 0.501 g l[superscript -1] h[superscript -1], respectively. In fed-batch production, initial sugar concentration of 100 g l[superscript -1] was used for cells production in the batch phase. At late-exponential phase which was reached at 18[superscript th]-22[superscript th] h, 200 g l[superscript -1] of sucrose was added. The best sorbitol yield and productivity were 50.1 g l[superscript -1] and 0.678 g l[superscript -1] h[superscript -1] respectively.